Системи розподілу потужності у повнопривідних автомобілях на основі електронно керованої муфти «Халдекс» - Кіндрацький, Богдан; Пелещишин, Олег (КІНПАТРІ ЛТД, 2013)
The construction of torque distribution systems between the front and rear axles wheel drive analyzed. A mathematical model for analysis and synthesis of such systems suggested.
Power distribution systems in four-wheel drive car based on electronic controlled coupling Haldex